Manajemen Pengolahan Data Penerima Bantuan Dana Program Keluarga Harapan (Pkh) pada Dinas Sosial Kabupaten Nabire, Papua - Tania Lensi Basinung; Gunawan Prayitno; Otniel Tipagau (STMIK Pesat Nabire, 2023)
Nabire Regency is located in Papua Province, Nabire is one of the largest districts in Papua. Pkh is one of the programs handled by the Nabire Social Service office. This program still requires good management so that no errors occur. Management is usually defined as a manager's function, namely planning, organizing, leadership, and controlling. So it can be said that management is a process. The lack of good management at the Nabire District Social Service can lead to inevitable mistakes such as multiple KK numbers, multiple names, different NIK numbers from the IDKTP, this happens because of human error that cannot be avoided. To avoid this problem, it is recommended for the government social service office to provide guarantees that can make the assistant section work well in order to minimize human errors, such as adequate rest time, food allowances while working or salary increases so that employees who input can be more careful in inputting.